Targeting tumor hypoxia in nasopharyngeal carcinoma. Issue 1 (22nd November 2011) - Hong, Bo; Lui, Vivian Wai Yan; Hashiguchi, Masumi; Hui, Edwin Pun; Chan, Anthony Tak‐Cheung
Abstract: Background: Nasopharyngeal carcinoma (NPC) is an endemic head and neck cancer in Southeast Asia. Although concurrent chemoradiotherapy generally results in good clinical response for early diseases, posttreatment relapse and distant metastasis are major causes for NPC deaths. There is an urgent need for more effective therapies for advanced NPC. Recent studies have demonstrated tumor hypoxia can be a therapeutic target in NPC. Methods: A Medline review of articles published on clinical and preclinical studies targeting tumor hypoxia was performed. Results: Studies published to date showed that tumor hypoxia is common in NPC and it is associated with disease progression and resistance to therapy. Several mechanisms have been proposed on the role of tumor hypoxia in NPC cell survival, angiogenesis, and metabolism. Studies reported by us and by others have demonstrated the therapeutic potential of targeting tumor hypoxia in NPC. Conclusions: Cumulative studies indicate that targeting tumor hypoxia could be an effective approach for NPC treatment. © 2011 Wiley Periodicals, Inc. Head Neck, 2013